THE EFFECT OF TEACHING STRATEGY ON STUDENTS’ ACHIEVEMENT IN LEARNING PHONOLOGY - Yani Lubis (VISION, 2019)
English Phonology is very difficult to study. Cause, there are many elements that have to master in studying it. Cooperative learning is a successful teaching strategy in which small teams, each with students or different levels of ability, use a variety of learning activities to improve their understanding of the subject. By applying Strategy that is hoped can progress the students’ achievement in learning English Phonology is the main points underlining in this study. The aims of this research are: (1) to know the students’ difficulties in learning Phonology, and (2) to know if there is effect of cooperative learning strategy on the students’ achievement in learning Phonology or not. Population is all members of well defined class of people, events or objects. the sample of the research are 57 students of Educational English Department 2017/2018. The students’ achievement in learning Phonology who taught by using cooperative learning strategy have higher score than the students’ achievement in learning Phonology who taught by using other strategy (conventional strategy). Event, the effect is not significant.